Medical resource consumption of moderate/severe psoriasis in a private health organization of Buenos Aires, Argentina, - María Laura Galimberti; Aldana S. Vacas; Barbara A. Hernández; María L. Bollea Garlatti; María J. Cura; Ricardo L. Galimberti (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Despite the economic burden of psoriasis for patients and societies, scant information exists regarding the impact and burden of the disease in Argentina. Objective: The objective of this study was to estimate medical resource consumption and direct health care costs for patients with moderate/severe psoriasis in Buenos Aires, Argentina from the perspective of the payer. Methods: Adults with moderate/severe psoriasis (severity was defined as receiving systemic treatment), during January 2010-January 2014, aged 18 years and older, members of the Italian Hospital Medical Care Program with at least 18 months of follow-up were included. All data on hospitalizations, drug prescription, outpatient episodes, consultations, and investigations/tests in the 12 months before inclusion in the study were considered for the estimation of medical resource consumption and direct health care costs. First-quarter 2018 costs were obtained from the IHMCP and converted into US dollars (using the January 2018 exchange rate). Results: A total of 791 patients were included. The mean age at diagnosis was 34 ± 12 years. Almost 65% of the patients had a dermatologist as their usual source of care, 43% had internists, and 14% had rheumatologists. The average yearly direct cost was US$ 5326 (95% CI: 4125-7896) per patient per year. Study limitation: The single center design and the retrospective nature are the main limitations. Conclusion: This is the first Argentine study that evaluated the costs of moderate/severe psoriasis by taking into consideration the direct medical costs of the disease.